1998
DOI: 10.4064/cm-76-2-279-294
|View full text |Cite
|
Sign up to set email alerts
|

On the equivalence of Ricci-semisymmetry and semisymmetry

Abstract: Introduction. A semi-Riemannian manifold (M, g), n = dim M ≥ 3, is said to be semisymmetric The semi-Riemannian manifold (M, g), n ≥ 3, satisfying (2) is called Riccisemisymmetric. There exist non-semisymmetric Ricci-semisymmetric manifolds. However, under some additional assumptions, (1) and (2) are equivalent for certain manifolds. For instance, we have the following statement.Remark 1.1. (1) and (2) are equivalent on every 3-dimensional semiRiemannian manifold as well as at all points of any semi-Riemannian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…It can be easily shown that the scalar curvature of the resulting manifold 3 , which is non-vanishing and non-constant. We shall now show that R 4 is a GK 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It can be easily shown that the scalar curvature of the resulting manifold 3 , which is non-vanishing and non-constant. We shall now show that R 4 is a GK 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be remarked here that some authors achieved Eq. (2.7) in their investigations about pseudo-Riemannian manifolds endowed with differential structures as [6,33,43,103]. However a study of its consequence on the structure of the Riemann and Weyl tensors and on Weyl's scalars and thus on the classification of space-times was pursued in [75-77, 83, 85].…”
Section: Proposition 22mentioning
confidence: 99%
“…A semi-Riemannian manifold (M, g) is then said to be semisymmetric if it satisfies the condition R · R = 0. It is well known that the class of semisymmetric manifolds includes the set of locally symmetric manifolds (∇R = 0) as a proper subset [2]; here, we suppose that (M, g) is a Riemmanian manifold. If M satisfies the condition ∇R = 0, then M is called a locally symmetric manifold.…”
Section: Preliminariesmentioning
confidence: 99%